2019
DOI: 10.1097/mph.0000000000001332
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult With Osteosarcoma of the Mandible and the Challenge in Management: Review of the Pediatric and Adult Literatures

Abstract: Neoadjuvant chemotherapy for osteosarcoma of the jaw (OSJ) remains controversial despite being a standardized treatment in osteosarcoma of the long bones. We present a case of a 22-year-old male with OSJ and performed a retrospective systemic review of previously published literatures of OSJ. We identified 27 articles: 7% recommended neoadjuvant chemotherapy, 22% recommended adjuvant chemotherapy, 19% recommended both neoadjuvant and adjuvant chemotherapy, 33% recommended against chemotherapy and 19% stated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…Osteosarcoma of the jaws accounts only for 6% to 7% of all osteosarcomas [6] , [3] . It represents approximately 0.2% of all malignancies [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteosarcoma of the jaws accounts only for 6% to 7% of all osteosarcomas [6] , [3] . It represents approximately 0.2% of all malignancies [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Dentists are the first to evaluate the lesion in 45% of cases. The diagnosis is often wrong leading to treatment of the lesion in 2/3 of cases with tooth extraction and half with antibiotics [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the anatomical location of mandibular osteosarcomas, dentists are the first to assess the lesion in 45% cases. Unfortunately, due to misdiagnosis, tooth extraction occurs in two third of cases and half of the patients are treated with antibiotics [8]. If osteosarcoma of the jaws is suspected, conventional radiographic studies and tomography and/or magnetic resonance imaging are recommended [9].…”
Section: Discussionmentioning
confidence: 99%
“…Craniofacial region is not a common site for OS development. OS of the jaws represents approximately 1% of head and neck malignancies and has lower grades and less distant metastases compared to the OS of the long bones but they have higher mortality with local disease which makes the importance of early diagnosis and treatment more crucial [13]. Prior radiotherapy is an important inducing factor for OS of the head and neck [14].…”
Section: Discussionmentioning
confidence: 99%
“…Ogunlewe et al reported data of patients with OS of the jaws in a 21-year period and suggested that there is a predominant incidence of mandible OS in the females, while OS of the maxilla presents a tendency to the males [12]. The most common symptoms are swelling, pain, ulceration, paresthesia and numbness of the lips [10,13].…”
Section: Os Of the Jaws Represents 2 To 10% Of Allmentioning
confidence: 99%